2022
DOI: 10.4049/immunohorizons.2100082
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Drift in Lupus-Prone MRL/lpr Mice: Potential Roles of MicroRNAs and Gut Microbiota

Abstract: MRL/lpr mice have been extensively used as a murine model of lupus. Disease progression in MRL/lpr mice can differ among animal facilities, suggesting a role for environmental factors. We noted a phenotypic drift of our in-house colony, which was the progeny of mice obtained from The Jackson Laboratory (JAX; stocking number 000485), that involved attenuated glomerulonephritis, increased splenomegaly, and reduced lymphadenopathy. To validate our in-house mice as a model of lupus, we compared these mice with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…We thus tested the levels of proteinuria, but no differences were found except for L. johnsonii , which significantly exacerbated glomerulonephritis over the PBS control ( Figure 1E ). Notably, the MRL/ lpr mice in our in-house colony, similar to those housed at The Jackson Laboratory, have lost the kidney disease phenotype ( 25 ), leading to low levels of proteinuria throughout the experiment. As expected, kidney histopathological analysis revealed no difference in glomerular and tubulointerstitial lesions as well as leukocyte infiltration ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus tested the levels of proteinuria, but no differences were found except for L. johnsonii , which significantly exacerbated glomerulonephritis over the PBS control ( Figure 1E ). Notably, the MRL/ lpr mice in our in-house colony, similar to those housed at The Jackson Laboratory, have lost the kidney disease phenotype ( 25 ), leading to low levels of proteinuria throughout the experiment. As expected, kidney histopathological analysis revealed no difference in glomerular and tubulointerstitial lesions as well as leukocyte infiltration ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We recently published a study where disease manifestations in MRL/ lpr mice can differ among animal facilities, suggesting a role for environment factors ( 25 ). Notably, the gene loci responsible for splenomegaly and lymphadenopathy, which are chromosomes 4, 5 and 7, are not the same as that for glomerulonephritis, which is chromosome 10.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been recently shown that Alcaligenaceae , Lachnospiraceae, and Ruminococcus torques groups had a tendency to causally decrease the risk of CKD [ 75 ]. Lower levels of Lachnospiraceae are linked to diseases such as splenomegaly, lymphadenopathy, glomerulonephritis, and other renal diseases [ 76 ]. Our finding of a strong correlation between low Lachnospiraceae abundance in GWI+ AB mice and higher miR-21 levels and kidney pathology provides a further mechanistic understanding of the risk of CKD in GWI veterans.…”
Section: Discussionmentioning
confidence: 99%
“…The connection between gut microbiota and lupus phenotype was further reinforced by the observation that a colony of MRL/lpr mice with a milder disease phenotype had an altered gut microbiota profile [23].…”
Section: Gut Bacterial Compositionmentioning
confidence: 99%
“…A total of 29 studies were included in this review, twelve of which used mouse models [14][15][16][17][18][19][20][21][22][23][24][25], fifteen included SLE patients [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], and two both [41,42].…”
Section: Characterization Of the Selected Studiesmentioning
confidence: 99%